Direct interaction of food derived colloidal micro/nano-particles with oral macrophages. (December 2017) - Ke, Lijing; Wang, Huiqin; Gao, Guanzhen; Rao, Pingfan; He, Lei; Zhou, Jianwu
Abstract Like any typical food system, bone soup (or broth), a traditional nourishing food in many cultures, contains a colloid dispersion of self-assembled micro/nano-particles. Food ingestion results in the direct contact of food colloidal MNPs with immune cells. Will they ever interact with each other? To answer the question, MNPs and NPs were separated from porcine bone soup and labeled with Nile Red, and their uptake by murine oral macrophages and its consequent effects were investigated. Colloidal particle samples of UF-MNPs and SEC-NP were prepared from porcine bone soup by ultrafiltration (UF) and size-exclusion chromatography, respectively. Their mean hydrodynamic diameters were 248 ± 10 nm and 170 ± 1 nm with dominant composition of protein and lipid. Particles in both samples were found to be internalized by oral macrophages upon co-incubation at particle/cell ratios of 14, 000/1. In normal oral macrophages, the particle uptake exerted influence neither on the cellular cytosolic membrane potential (V mem ) nor mitochondrial superoxide level, as were indicated with fluorescent dyes of DiBAC4 (3) and MitoSOX Red, respectively. However, when oral macrophages were challenged by peroxyl radical inducer AAPH, the engulfment of UF-MNPs and SEC-NPs mitigated the peroxyl radical induced membrane hyperpolarization effect by up to 70%, and the suppression on the oxygen respiration in mitochondria by up to 100%. Those results provide evidence of the direct interaction between food colloidal particles with immune cells, implying a possible new mode of food-body interaction. Food ingestion: Colloidal particles derived from bone soup interact with immune cells The uptake of food colloidal particles by oral macrophages can mitigate the peroxyl radical induced membrane hyperpolarization effect and suppress the oxygen respiration in mitochondria. Jianwu Zhou and coworkers from Zhejiang Gongshang University, China, separated micro/nano particles of 248 ± 10 nm and 170 ± 1 nm in diameter from porcine bone soup via membrane ultrafiltration and gel-filtration, respectively. By labeling the colloidal particles with hydrophobic fluorescent dyes, they tracked their internalization by oral macrophages upon co-incubation. It was found the food colloidal particles ingestion had no influence on the cell plasma membrane potential and mitochondrial superoxide level of the normal oral macrophages. However, when macrophages were irritated by peroxyl radical inducer 2, 2′-azobis (2-amidinopropane) dihydrochloride, the food micro/nano particles exhibited a pacifying effect. This finding reveal a possible new mode of food-body interaction.